2021
DOI: 10.25259/jish_15_2021
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control study for evaluating the efficacy of individualized homoeopathic medicine as an adjuvant therapy in mild to moderate cases of COVID-19

Abstract: Objectives: Understanding the efficacy of indicated homoeopathic medicine as an adjuvant to standard treatment in improving the subjective and objective parameters in patients with mild to moderate confirmed cases of COVID-19. Materials and Methods: Study design: A prospective randomized control trial conducted at Deenanath Mangeshkar Hospital, Erandwane, Pune, wherein Group A received standard treatment along with indicated homoeopathic medicine (experimental group) and Group B received the standard treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, this study showed the use of remedies like Arsenicum album, Bryonia alba and Phosphorus in the majority, whereas current study evidences the exceptional effect of Bryonia alba, Tuberculinum bovinum and Arnica montana. Another randomized controlled trial of 50 sample sizes conducted on mild to moderate cases of COVID-19 promises the role of Homoeopathic medicines in relieving subjective as well as objective parameters [37]. Also, prognostic factor research carried out as a multicentric observational study at public health care-clinics, showed the efficacy of homoeopathy in improvement of case of COVID-19 with frequent indications of Arsenicum album, Bryonia alba, Gelsemium sempervirens, and Pulsatilla nigricans [24].…”
Section: Interpretation Of Findings In Relation To Previous Publicati...mentioning
confidence: 99%
“…Moreover, this study showed the use of remedies like Arsenicum album, Bryonia alba and Phosphorus in the majority, whereas current study evidences the exceptional effect of Bryonia alba, Tuberculinum bovinum and Arnica montana. Another randomized controlled trial of 50 sample sizes conducted on mild to moderate cases of COVID-19 promises the role of Homoeopathic medicines in relieving subjective as well as objective parameters [37]. Also, prognostic factor research carried out as a multicentric observational study at public health care-clinics, showed the efficacy of homoeopathy in improvement of case of COVID-19 with frequent indications of Arsenicum album, Bryonia alba, Gelsemium sempervirens, and Pulsatilla nigricans [24].…”
Section: Interpretation Of Findings In Relation To Previous Publicati...mentioning
confidence: 99%
“…27 Homeopathy, which works on principles of similar symptomatology of disease and drug, individualization of therapy and hyper-attenuated prescriptions, requires a special research method. [28][29][30] Various publications have tried registry and randomized trial-based evidence of the efficacy of individualized homeopathic medicines or genus epidemicus in different ways, either as a standalone therapy or as an adjuvant. 31 With an emerging acceptance in population despite anecdotal criticism by perpetually repudiating experts, there is still a pronounced need for organized efforts to establish the safety and effectiveness of homeopathy in COVID-19 patients, scientifically.…”
mentioning
confidence: 99%